AN ENERGY SYSTEM SIMULATION OF TURKEY WITH A 50% RENEWABLE ENERGY SCENARIO - (:unkn) unknown (My University, 2021)
Decreasing the usage of fossil fuels in the electricity production is a tough challenge for countries. The world is still depended on fossil fuels to generate electricity. Increasing the share of renewable energy systems in electricity production is significant in many aspects such as lower CO2 emissions, grid flexibility, decentralizing, etc. Nowadays, many countries shape their energy policies and strategies to use more renewable and indigenous resources. Turkey is one of these countries and has ambitions goals to use more domestic sources to produce electricity. Turkey generally aims to reduce the usage of imported energy sources in electricity generation. Thus this paper investigates the share of 50% renewable energy system (RES) simulation in the electricity production via the EnergyPLAN model. An energy system analysis was conducted in a 50% renewable scenario in 2023. The main target of this scenario is to perform a 50% renewable energy system in electricity production. A reference year is 2018 and the results of the 50% RES scenario were compared with a reference scenario. A main focus of this study is to investigate aspects of carbon emissions, RES share, and costs between the scenarios for the years 2018 and 2023.

Elektrik üretiminde fosil yakıt kullanımının düşürülmesi zor bir süreçtir. Tüm dünya hala elektrik üretiminde fosil yakıtlara bağlı durumdadır. Güç üretiminde yenilenebilir enerji payının arttırılması, CO2 emisyonunun düşürülmesi, şebeke esnekliğinin sağlanması ve merkezi olmayan elektrik üretimi gibi birçok yönden avantaj sağlamaktadır. Günümüzde birçok ülke enerji stratejilerini ve politikalarını daha fazla yerli ve yenilenebilir kaynakların kullanımı şekillendirmektedir. Türkiye de bu ülkelerden birisidir ve elektrik üretiminde daha fazla yerli kaynak kullanımı için etkili politikalara sahiptir. Türkiye genel olarak elektrik üretiminde ithal enerji kaynaklarının kullanımını düşürmeyi hedeflemektedir. Bu makalede EnergyPLAN modeli ile 2023 için %50 yenilenebilir enerji sistemi simülasyonu incelenmiştir. Enerji sistem analizi, 2023 için %50 yenilenebilir enerji sistem senaryosu üzerine kurulmuştur. Bu senaryodaki temel hedef, elektrik üretiminde %50 yenilenebilir enerji kullanımını gerçekleştirmektir. Bu çalışmada referans yıl ise 2018 olarak seçilmiştir ve 2023 senaryosunun sonuçları ile kıyaslanmıştır. Bu çalışmanın odağı 2018 ve 2023 senaryolarının yenilenebilir enerji payı, CO2 emisyonu ve maliyetler yönünden incelenmesidir.
% 50 YENİLENEBİLİR ENERJİ SENARYOSU İLE TÜRKİYE’NİN ENERJİ SİSTEM SİMÜLASYONU